Dall'analisi fenomenologica alla verifica sperimentale in psicologia: indagini sui meccanismi di difesa psichica in ambito educativo - Valeria Biasi (LED Edizioni Universitarie, 2014)
From Phenomenogical Analysis to Experimental Verification in Psychology: Studies on Psychic Defence Mechanisms in the Educational Field The present contribution examines the shift from introspective analysis, based on the phenomenological method, to the evaluation of introspective data collected by means of empirical methods, which go to define so-called «experimental Phenomenology», all within a perspective of the integration between experimental phenomenology and psychodynamic assumptions. This examination is conducted here with regard to psychological defence mechanisms and delineates the opposing processes of «perceptual defence» and «emphasizing» (facilitation, accentuation). After describing the main results achieved in the perceptological domain, where it is possible to adopt an orthodox experimental protocol, the attention shifts to field studies in the educational field regarding the teacher-student relation, according to an empirical methodology enabling a «quantification» of the presence of specific defence mechanisms which can arise in the educational relation, such as the overestimation or underestimation of phenomenal qualities attributed to oneself and/or to the other. Besides confirming the main dynamics of accentuation (overestimation) and defence (underestimation) demonstrated experimentally in laboratory studies, the contribution provides an example of the quantification of an essentially qualitative concept as the «defence mechanism», as is clear from its very definition: a defence mechanism is any behavioral strategy or attitude aimed at reducing and/or preventing subjectively perceived pain and suffering. This is a good opportunity, from a methodological standpoint, to demonstrate how it is possible to quantify strongly subjective variables in order to obtain an empirical verification, which is essential for arriving at scientifically credited knowledge.